2011
DOI: 10.1161/circulationaha.110.960898
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cardiac Resynchronization Therapy by QRS Morphology in the Multicenter Automatic Defibrillator Implantation Trial–Cardiac Resynchronization Therapy (MADIT-CRT)

Abstract: on behalf of the MADIT-CRT InvestigatorsBackground-This study aimed to determine whether QRS morphology identifies patients who benefit from cardiac resynchronization therapy with a defibrillator (CRT-D) and whether it influences the risk of primary and secondary end points in patients enrolled in the Multicenter Automatic Defibrillator Implantation Trial-Cardiac Resynchronization Therapy (MADIT-CRT) trial. Methods and Results-Baseline 12-lead ECGs were evaluated with regard to QRS morphology. Heart failure ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
490
1
41

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 746 publications
(554 citation statements)
references
References 31 publications
22
490
1
41
Order By: Relevance
“…The presence of right bundle branch block morphology was independently associated with the composite primary outcome of all‐cause mortality and unplanned hospitalization for management of major cardiovascular events (HR 2.043, 95% CI 1.332–3.157; P  = 0.001) 6. In addition, the sub‐study of the Multicenter Automatic Defibrillator Implantation Trial‐Cardiac Resynchronization Therapy (MADIT‐CRT) trial, including 1817 patients with sinus rhythm at baseline ECG, showed that the presence of LBBB morphology was associated with a 53% reduction in the risk of heart failure events or all‐cause mortality of patients randomized to CRT with defibrillator compared with patients treated with implantable cardioverter defibrillator (ICD) alone whereas patients with non‐LBBB QRS morphology did not show clinical benefit from CRT 7. Subsequent meta‐analysis pooling data from 5356 patients enrolled in four randomized trials showed that LBBB morphology was associated with significant reduction in the composite adverse clinical events of patients treated with CRT (risk ratio 0.64, 95% CI 0.52–0.77; P  < 0.0001) whereas patients with non‐LBBB configuration failed to show clinical benefit 9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of right bundle branch block morphology was independently associated with the composite primary outcome of all‐cause mortality and unplanned hospitalization for management of major cardiovascular events (HR 2.043, 95% CI 1.332–3.157; P  = 0.001) 6. In addition, the sub‐study of the Multicenter Automatic Defibrillator Implantation Trial‐Cardiac Resynchronization Therapy (MADIT‐CRT) trial, including 1817 patients with sinus rhythm at baseline ECG, showed that the presence of LBBB morphology was associated with a 53% reduction in the risk of heart failure events or all‐cause mortality of patients randomized to CRT with defibrillator compared with patients treated with implantable cardioverter defibrillator (ICD) alone whereas patients with non‐LBBB QRS morphology did not show clinical benefit from CRT 7. Subsequent meta‐analysis pooling data from 5356 patients enrolled in four randomized trials showed that LBBB morphology was associated with significant reduction in the composite adverse clinical events of patients treated with CRT (risk ratio 0.64, 95% CI 0.52–0.77; P  < 0.0001) whereas patients with non‐LBBB configuration failed to show clinical benefit 9.…”
Section: Discussionmentioning
confidence: 99%
“…However, the individual prognostic benefit is not consistent, and selection of patients who will benefit from CRT remains challenging. Sub‐analyses from randomized controlled trials and meta‐analyses pointed out that QRS duration and morphology are relevant for prognosis of patients treated with CRT 5, 6, 7, 8, 9. Patients with shorter QRS duration and/or non‐left bundle branch block (LBBB) morphology appear to benefit less than patients with longer QRS duration and/or LBBB morphology 5, 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En general, con estimulación cardiaca, el índice de recurrencia del síncope durante el seguimiento osciló entre 0 y el 20%, mientras que las recurrencias del síncope siempre fueron más en los pacientes no tratados, que mostraron tasas de un 20-60%. En un metanálisis de los tres estudios con grupo control de pacientes no tratados [36][37][38] , el síncope se repitió en el 9% de los 85 pacientes tratados con marcapasos y en el 38% de los 91 controles (riesgo relativo [RR] = 0,24; intervalo de confianza del 95% [IC95%], 0, 48). En un registro amplio de 169 pacientes consecutivos tratados con marcapasos 39 , la recurrencia actuarial estimada de síncope fue del 7% a 1 año, el 16% a 3 años y el 20% a 5 años.…”
Section: Síncope Del Seno Carotídeo (Recomendación 1)unclassified
“…Those with left bundle branch block (LBBB) and the widest QRS complexes seem to have the highest rate of response [4]. However, a significant percentage of patients with guideline-approved criteria remain "nonresponders."…”
mentioning
confidence: 99%